2021
DOI: 10.2147/ott.s296373
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Profiling Identifies CCNA2 as a Potential Biomarker of Immunotherapy in Breast Cancer

Abstract: Introduction Breast cancer is the main reason for cancer-related deaths in women and the most common malignant cancer among women. In recent years, immunosuppressive factors have become a new type of treatment for cancer. However, there are no effective biomarkers for breast cancer immunotherapy. Therefore, exploring immune-related biomarkers is presently an important topic in breast cancer. Methods Gene expression profile data of breast cancer from The Cancer Genome At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Basic research in areas such as tumor genomics, RNA-omics, and proteomics is expanding application in clinical practice. Molecular pathological diagnosis is becoming increasingly important for early diagnosis, drug efficacy evaluation, and prognostic testing of BRCA, gradually changing the traditional empirical treatment model to an individual-body treatment model based on biomarkers [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Basic research in areas such as tumor genomics, RNA-omics, and proteomics is expanding application in clinical practice. Molecular pathological diagnosis is becoming increasingly important for early diagnosis, drug efficacy evaluation, and prognostic testing of BRCA, gradually changing the traditional empirical treatment model to an individual-body treatment model based on biomarkers [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Herein, based on an integrative analysis of diverse RNAs from different datasets, CCNA2/MKI67/KIF11:miR-30a-5p: VPS9D1-AS1 axis-related cell cycle is identified as a potential prognostic marker via constructing a ceRNA network and indepth analysis, and all of them are characterized as crucial RNAs in the occurrence and development of LUAD. Of the three mRNAs, CCNA2 has been studied because of its role in cancer, including its prognostic value in breast cancer (54)(55)(56), colorectal cancer (57), pancreatic cancer (58), LUAD (59), gastric cancer (60), bladder cancer (61), etc. MKI67, a marker gene in the cell cycle, also has been reported with prognostic value in NSCLC (62) and breast cancer (63).…”
Section: Discussionmentioning
confidence: 99%
“…CCNA2 is over-expressed in a variety of human malignancies, suggesting its potential role in cancer transformation and progression. The study found that CCNA2 expression was significantly high in carcinoma tissues than in normal controls, and CCNA2 was considered as a potential immunotherapy marker in breast cancer [ 17 ]. Meanwhile, some studies have shown that CCNA2 can be used for the early detection and prognosis of colon cancer [ 18 ].…”
Section: Discussionmentioning
confidence: 99%